Self‐Renewal of Bone Marrow Stem Cells by Nanovesicles Engineered from Embryonic Stem Cells. Issue 24 (10th November 2016) - Jo, Wonju; Jeong, Dayeong; Kim, Junho; Park, Jaesung
Abstract : Extracellular vesicles can enhance cell proliferation by stimulating signal transduction and delivering genetic materials, and thus may have applications in regenerative medicine and other therapeutic applications. The processes employed to isolate extracellular vesicles, however, are complex and achieve low yield. To overcome these obstacles, a large‐scale, micropore device for generating extracellular vesicle‐mimetic nanovesicles that have characteristics similar to those of extracellular vesicles is fabricated. The nanovesicles are generated through the self‐assembly capability of cell membrane fragments in an aqueous solution. The nanovesicles enhance the proliferation of murine mesenchymal stem cells (MSCs), stimulate the signal pathway related to cell proliferation, and do not influence the characteristics of murine MSCs. Therefore, these nanovesicles could provide stable MSCs for regenerative medicine and other therapeutic applications. Abstract : Extracellular vesicle‐mimetic nanovesicles (NVs) from embryonic stem cells (ESCs) are fabricated, and it is demonstrated that the NVs have specific functions in cell proliferation by comparing the proliferation after treatment of various nanoparticles on mouse mesenchymal stem cells. NVs from ESCs are effective in stimulating cell proliferation, and may have important functions in regenerative medicine.